Experimental investigation on the effects of channel material, size, and oil viscosity in horizontal mini-channels - Bultongez, Kevin Kombo (Kansas State University, 2017)
Oil-water separation is an important process in the petroleum industry. This research investigates the use of surface tension forces to improve current oil-water separation technologies. An understanding of oil-water flows in surface tension driven mini-channels is necessary. This work investigates the effects of mini-channel wall material and tube diameter, along with oil viscosity, on flow regimes and pressure drops in mini-channel oil-water flows. A horizontal closed-loop, adiabatic experimental apparatus was constructed and validated using single-phase water. 2.1-mm and 3.7-mm borosilicate glass, 3.7-mm stainless steel and 4.0-mm Inconel tubes, resulting in Eötvös numbers of 0.2, 0.6 and 0.7 were tested. The experimental data were analyzed and compared using two mineral oils (i.e., Parol 70 and 100) with densities of 840 kg/m³ for both and viscosities of 11.7 and 20.8 mPa-s, respectively. Experiments included a wide range of oil superficial velocities (e.g., 0.28-6.82 m/s for glass, 0.28-2.80 m/s for stainless steel and 0.21-2.89 for Inconel) and water superficial velocities (e.g., 0.07-6.77 for glass, 0.07-4.20 m/s for stainless steel and 0.06-3.86 m/s). Flow regimes were observed and classified as stratified, annular, intermittent, and dispersed flow regimes. Effects of tube diameter were observed. For example, the 2.1-mm glass tube had the smaller range of stratified flows and the larger range of annular and intermittent flows compared to the 3.7-mm glass tube. At the same oil and water superficial velocities and relatively the same flow regime, stainless steel and Inconel always displayed higher pressure drop than the glass tube. However, pressure drops were a strong function of flow regime; lowest pressure drops were found for annular flows and highest pressure drops for dispersed flows. Flow regime maps and pressure drop graphs were created. Overall effects of oil viscosity were modest; however, an increase in oil viscosity enhanced flow stability which affected flow regime transition points.
Keywords: Flow regime; Oil-water; Micro and mini-channel; Eötvös number